-4=3x+7(-x-4)

Simple and best practice solution for -4=3x+7(-x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=3x+7(-x-4) equation:


Simplifying
-4 = 3x + 7(-1x + -4)

Reorder the terms:
-4 = 3x + 7(-4 + -1x)
-4 = 3x + (-4 * 7 + -1x * 7)
-4 = 3x + (-28 + -7x)

Reorder the terms:
-4 = -28 + 3x + -7x

Combine like terms: 3x + -7x = -4x
-4 = -28 + -4x

Solving
-4 = -28 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-4 + 4x = -28 + -4x + 4x

Combine like terms: -4x + 4x = 0
-4 + 4x = -28 + 0
-4 + 4x = -28

Add '4' to each side of the equation.
-4 + 4 + 4x = -28 + 4

Combine like terms: -4 + 4 = 0
0 + 4x = -28 + 4
4x = -28 + 4

Combine like terms: -28 + 4 = -24
4x = -24

Divide each side by '4'.
x = -6

Simplifying
x = -6

See similar equations:

| 15x+10=8x+38 | | -2x-8=-5x+28 | | 9(2n-1)=(8n+4)+3 | | 2(x-1)=24 | | 93=-6x+3(-2x-13) | | 8x-12+7=-3 | | 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a | | 4(3x-5)+x= | | 10x+5(z-12)=0 | | -3x-10=-2x+4 | | 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 | | x+2x+2x-30=5400 | | 8-n-3n=6 | | -6x+2y=5 | | 6x-2(-6x+3)=120 | | 2x+20=-3x+50 | | 4(x-3)+7=-3 | | 7x+2(3x+7)=144 | | 6x^2+9x-4=38 | | ax^3+bx-5=0 | | D+8=-7 | | -4(n-b)=12 | | 9(n+6)-5(2+2n)=-8n+5n | | 5(x+4)+14=59 |

Equations solver categories